2006
DOI: 10.1111/j.1600-0854.2006.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Setting SNAREs in a Different Wood

Abstract: Vesicle traffic is essential for cell homeostasis, growth and development in plants, as it is in other eukaryotes, and is facilitated by a superfamily of proteins known as soluble N-ethylmaleimide-sensitive fusion protein attachment protein receptors (SNAREs). Although SNAREs are well-conserved across phylla, genomic analysis for two model angiosperm species available to date, rice and Arabidopsis, highlights common patterns of divergence from other eukaryotes. These patterns are associated with the expansion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 92 publications
(130 reference statements)
0
74
0
Order By: Relevance
“…In plants, sequence comparison allowed the identification of rice orthologs for most of the Arabidopsis Q-SNAREs (Sutter et al, 2006a). Our observation that SYP121-Sp2 fragments from Arabidopsis and maize decreased the plasma membrane trafficking of mYFP:ZmPIP2;5 in tobacco epidermal cells and maize mesophyll protoplasts demonstrates that the mechanism of SYP121-mediated plasma membrane anchoring of PIP2 aquaporins is conserved between monocots and dicots.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In plants, sequence comparison allowed the identification of rice orthologs for most of the Arabidopsis Q-SNAREs (Sutter et al, 2006a). Our observation that SYP121-Sp2 fragments from Arabidopsis and maize decreased the plasma membrane trafficking of mYFP:ZmPIP2;5 in tobacco epidermal cells and maize mesophyll protoplasts demonstrates that the mechanism of SYP121-mediated plasma membrane anchoring of PIP2 aquaporins is conserved between monocots and dicots.…”
Section: Discussionmentioning
confidence: 68%
“…Genome analysis showed that the SNARE family is larger in plants than in other eukaryotes (Sanderfoot, 2007). Indeed, more than 60 SNARE isoforms have been identified in the Arabidopsis genome, and orthologs are found in rice (Oryza sativa) for most of them, supporting the idea that they are conserved between monocots and dicots (Sutter et al, 2006a). Syntaxins belong to the Q-SNARE subfamily and, in Arabidopsis, seven of them localize to the plasma membrane and are involved in traffic at this membrane .…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, it remains unclear how the remarkable morphological diversity of eukaryotes is reflected in their SNARE repertoires. For example, so far the highest number of SNARE proteins was discovered in green plants (Sanderfoot et al, 2000;Sutter et al, 2006;Sanderfoot, 2007), but it is unclear so far whether the additional SNAREs mediate novel trafficking steps or whether they are simply variations in the given repertoire. This calls for an exhaustive comparison of SNARE repertoires in different organisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the original classification of SNARE proteins (Bock et al, 2001) was based on only ϳ100 sequences from only few organisms and did not include some more diverged SNARE types (Lewis et al, 1997;Lewis and Pelham, 2002;Burri et al, 2003;Dilcher et al, 2003). In the subsequent years, additional complete genomes shed more light onto the conservation of the SNARE machinery, yet some SNAREs, in particular from protists, appeared to be rather atypical (Sanderfoot et al, 2000; Doolittle, 2002, 2004;Gupta and Brent Heath, 2002;Uemura et al, 2004;Besteiro et al, 2006;Schilde et al, 2006;Sutter et al, 2006;Ayong et al, 2007;Kissmehl et al, 2007;Sanderfoot, 2007). These studies, however, did not provide a universal classification scheme, as usually only a subset of sequences was examined.…”
mentioning
confidence: 99%